Environmental hedging: A theory and method for reconciling reservoir operations for downstream ecology and water supply. Issue 9 (10th September 2017) - Adams, L. E.; Lund, J. R.; Moyle, P. B.; Quiñones, R. M.; Herman, J. D.; O'Rear, T. A.
Abstract: Building reservoir release schedules to manage engineered river systems can involve costly trade‐offs between storing and releasing water. As a result, the design of release schedules requires metrics that quantify the benefit and damages created by releases to the downstream ecosystem. Such metrics should support making operational decisions under uncertain hydrologic conditions, including drought and flood seasons. This study addresses this need and develops a reservoir operation rule structure and method to maximize downstream environmental benefit while meeting human water demands. The result is a general approach for hedging downstream environmental objectives. A multistage stochastic mixed‐integer nonlinear program with Markov Chains, identifies optimal "environmental hedging, " releases to maximize environmental benefits subject to probabilistic seasonal hydrologic conditions, current, past, and future environmental demand, human water supply needs, infrastructure limitations, population dynamics, drought storage protection, and the river's carrying capacity. Environmental hedging "hedges bets" for drought by reducing releases for fish, sometimes intentionally killing some fish early to reduce the likelihood of large fish kills and storage crises later. This approach is applied to Folsom reservoir in California to support survival of fall‐run Chinook salmon in the lower American River for a range of carryover and initial storage cases. Benefit is measured in terms of fish survival; maintaining self‐sustaining native fish populations is a significant indicator of ecosystem function. Environmental hedging meets human demand and outperforms other operating rules, including the current Folsom operating strategy, based on metrics of fish extirpation and water supply reliability. Key Points: A new approach for operating reservoirs to support the downstream ecology of regulated rivers is developed called "environmental hedging" Environmental hedging maximizes downstream biological success with seasonal uncertainty while meeting human water demands Folsom Dam operations modeled with hedging outperform other policies, including current practice, for environment and water supply metrics